Chapter 3 Droit de cité The Digital Lab as Digital Milieu - Smithies, James (Taylor & Francis, 2024)
When King's Digital Lab was established in late 2015 it was conceived as both a craft factory (working with colleagues to produce digital outputs) and a technical experiment (a site where the intersection of technology and the humanities could be explored). Significant progress has been made on both of those fronts: dozens of projects have been enabled, operational white papers have been shared, and research outputs have explored the intellectual and philosophical aspects of the laboratory environment. It is now possible to move beyond the techniques that enabled this success and use insights from the philosophy of technology to explore long-standing concerns about the role of technology in society. In doing so, the laboratory would become an applied techno-philosophical experiment. More radically, it could rehabilitate the use of technical objects in the humanities and reject technophobia as not only unproductive but unethical. Technical (digital) objects could thus be accorded droit de cité in the field of the humanities. This perspective fits well with emerging work in the humanities that highlights the history of the field, its relationship to modelling, the indeterminacy of computer technology, and the potential for human-machine relations to be reconciled through aesthetics.